COMBINING ABILITY AND HETEROSIS IN MAIZE (Zea mays L.) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
A line × tester analysis was conducted in maize involving 12 lines and 3 testers for grain yield and its components to determine the heterosis as well as general combining ability (GCA) and specific combining ability (SCA) effects. Highly significant genotypic differences were observed indicated wide range of variability present among the genotypes. GCA and SCA variance for yield per plant number of kernels per row and 100-kernels weight were observed significant, which indicated importance of additive as type of gene action for these characters. The ratio of SCA and GCA variances were high for the all character studied that revealed the preponderance of non additive type of gene action. Standard heterosis ranged from -28.29 to 28.41%; -12.29 to 24.38%; -1.11 to 24.44%; -14.75 to 6.67%; -17.24 to 11.26% and -10.94 to 20.83% for grain yield per plant, number of grains per row, number of rows per ear, ear length, ear diameter and 100-kernel weight, respectively. The lines IPB 911-16, IPB 911-12, IPB 911-2, IPB 911-18 and IPB 911-47 showed significant positive GCA effect and simultaneously possessed high mean value indicating that the per se performance of the parents could prove as an useful index for combining ability. The crosses exhibited significant SCA effects involved high x high, high x low, low x high, average x low and low x low general combining parents. The cross combinations with significant positive SCA effect having high mean values might be used for obtaining high yielding hybrids. The information on the nature of gene action with respective variety and characters might be used depending on the breeding objectives.DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17045